Langkah Komunikasi Persuasif Epistema Institute dalam Mendorong Lahirnya Perda Kasepuhan Lebak - Ruhimat Ruhimat (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2022)
This study aims to find out how advocacy communication Epistema Institute in encouraging the formation of regional regulations about kasepuhan. The method used in this research is qualitative method with case study design. Data collection was done by in-depth interview technique and library Studies. Data analysis is done by using inductive analysis. The results of this study indicate that advocacy communications conducted by Epistema Institute through stages of communication advocacy of Epistema Institute are formulating issues, formulating long-term goals and strategic objectives, determining advocacy targets, building support, developing messages, selecting information channels, implementation, and monitoring and evaluation. Stages carried out to the local government namely Lebak district council and kasepuhan community as an informant in this study. With persuasive message delivery approach and effective communication action, Epistema Institute succeeded in encouraging Local Government, DPRD, to form Regional Regulation Lebak Distric of Banten Province Number 8 Year 2015 on Recognition, Protection and Empowerment of Kasepuhan Customary Law Community.